Influence of crop management practices in two locations on plantain response to plant parasitic nematodes - Olaniyi, M.; Speijer, P.; Waele, D. de; Swennen, Rony L.; Tenkouano, A. (2006)
Mulch supported more vigorous plants and repressed nematode activity. Plant parasitic nematodes were responsible for damage to the roots of plantain cv. Agbagba, resulting in reduction in the number of functional leaves on the plants. Inoculated plants had better suckering than the uninnoculated ones when mulched, suggesting that the cumulative effect may result in heavier toppling in the inoculated plots during later growth stage, especially at flowering and fruit filling when the roots of the suckers might have been progressively destroyed by the nematodes.